2019
DOI: 10.1111/bcp.14031
|View full text |Cite
|
Sign up to set email alerts
|

The importance of both CYP2C19 and CYP2B6 germline variations in cyclophosphamide pharmacokinetics and clinical outcomes

Abstract: Cyclophosphamide is an alkylating agent used in the treatment of solid and haematological malignancies and as an immunosuppressive agent. As a prodrug, it is dependent on bioactivation to the active phosphoramide mustard metabolite to elicit its therapeutic effect. This focused review will highlight the evidence for the role of germline pharmacogenetic variation in both plasma pharmacokinetics and clinical outcomes. There is a substantial indication from 13 pharmacokinetic and 17 therapeutic outcome studies, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…Determination of the type of drug metabolism rate can be seen phenotypically based on the bioactivity ratio value, 11 but no literature has published for the classification of the three types of CP 4-hydroxylation rate (PM, EM, and UM) with the limiting value of the bioactivity ratio. Previously it has been agreed in some literature that CYP2B6 wild type is categorized as extensive metabolizer (EM) type.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Determination of the type of drug metabolism rate can be seen phenotypically based on the bioactivity ratio value, 11 but no literature has published for the classification of the three types of CP 4-hydroxylation rate (PM, EM, and UM) with the limiting value of the bioactivity ratio. Previously it has been agreed in some literature that CYP2B6 wild type is categorized as extensive metabolizer (EM) type.…”
Section: Resultsmentioning
confidence: 99%
“…From several studies, CYP2B6 *6 allele variant carrier had greater 4-hydroxylation activity than noncarriers. 11 , 20–22 However, in a study on Japanese patients, correlation between the CP 4-hydroxylation rate with CYP2B6 *6 and *9 alleles was not found. 6 Differences between study results might be due to several factors including ethnicity, number of subjects, CP dose, or co-medication.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…To the best of our knowledge, the effects of patient factors, such as sex, BSA, and biochemistry covariates, on VCR CL in elderly patients have not yet been clarified. Recently, it has been reported that gene polymorphisms of drug-metabolizing enzymes or transporters affect the pharmacokinetics of these cytotoxic anticancer drugs 23,[27][28][29][30] . Thus, various factors have a potential impact on the pharmacokinetic exposure of elderly patients receiving CHOP therapy.…”
Section: Discussionmentioning
confidence: 99%